African refugee women in Egypt: lacunae in international refugee law and the erasure of disadvantaged groups - Mohamad, Wigdan (AUC Knowledge Fountain, 2020)
Migration is not a recent phenomenon. From the first humans, to people all around the globe today, leave their homes in search of a better life. Since February 2020, Egypt, an attractive destination due to its strategic geolocation, homes the “fifth largest urban refugee population in the world ”. Persecution, political instability, climate degradation, protracted conflicts, unrest, and new wars throughout Africa and Middle Eastern region has caused a dramatic rise of refugees, many of whom make their way to Egypt with the hopes of finding refuge. Egypt hosts a diverse community of refugees, asylum-seekers, and failed asylum-seekers from 58 different countries around the world. Many of these are African refugees, who come from diverse cultural, religious, and socio-economic backgrounds. The experience of Black African refugee women differs greatly from other refugee groups. Using this group as a starting point, and using their multidimensional experience, while locating this experience within the legal frameworks that govern refugees in Egypt, this paper aims to illustrate the erasure of this group within these frameworks, which further perpetuates the consequent oppression due to this erasure. Single-axis categories , such as the categories which must be “satisfied” across all refugee law instruments (international, national, domestic, bilateral), forces us to neglect the overlooked subordination of groups that do not fulfil these categories singularly, due to their intersectional identities. Single-axis categories forces groups that fit outside of these groups to essentially disappear, and when they do, they become invisible, causing their identification and potential remedial measures to disappear as well. This paper will demonstrate that African refugee women in Egypt, due to their intersecting identities of Black, refugee and women, are multi-burdened, and thus face a particular type of oppression that occurs due to the lacunae which occurs when the intersecting legal frameworks fail to address their multidimensional identities, their needs, and consequential oppression. The formal equality provided to all refugees “in general” via international, national, domestic and bilateral refugee law instruments inadvertently perpetuates inequality toward another group: Black refugee women. Using intersectionality theory as a lens, it will be argued that the intersecting legal frameworks that govern refugees in Egypt perpetuate the oppression faced by Black refugee women by failing to address the interwoven prejudices that they face due to their multidimensional identity, which create interdependent and overlapping system of discrimination and disadvantage.